(untitled) (Economics and region, 2024)
The article focuses on the need to develop creative industries of cities and regions as an impetus to increase the economic potential of territories and expand the range of goods and services produced within territories and translate the local identity of territories into the global world. It has been concluded that the main characteristic of creative industries is the presence of a source of individual creativity, skills and talents with the potential to create jobs and well-being through the production and operation of intellectual property. A number of positive effects of the development of creative industries (economic, social, cultural, innovative) were highlighted, which makes it possible to flexibly enter the new economic reality and contributes to the implementation of mechanisms for creating the creative potential of cities and regions. Undoubtedly, today creativity is becoming the driving force of economic growth and innovation in the post-industrial economy, especially important for the strategic goals of the non-raw material economic orientation of Russia. Thus, S. Novikova concludes that the creative economy is a modern progressive form of socio – economic development based on the intellectual and creative dominance of Labor and capital.. The economy and society are now experiencing an active process of digital transformation, which greatly transforms economic reality, complementing it with the potential of artificial intelligence, robotics, virtual reality, highly developed competencies, technologies of creative thinking. We believe that in modern conditions, research aimed at creating and implementing stimulating conditions and factors of production for the development of creative industries that give a powerful impetus to economic progress is gaining particular relevance. Let us turn to the methodology for studying the main features of creative industries in economics. In a number of scientific publications, creative industries are called "Cognition", which acts as the main influential factor in the development of the knowledge economy. Undoubtedly, the increase in knowledge is the main source of increasing human well-being. J. According to Mokyr, analyzing the history of human creative activity, an increase in the volume of knowledge is the result of people’s persistent desire for invention and innovation, even in the absence of institutional incentives. Structural and price changes in factor markets have changed incentives to gain new knowledge about the means of production.